Can intervention work? - Stewart, Rory. (New York W. W. Norton & Co, 2011)
A fresh and critically important perspective on foreign interventions? (Washington Post), Can Intervention Work? distills Rory Stewart?s (author of The Places In Between) and Gerald Knaus?s remarkable firsthand experiences of political and military interventions into a potent examination of what we can and cannot achieve in a new era of nation building. As they delve into the massive, military-driven efforts in Bosnia, Iraq, and Afghanistan, the authors reveal each effort?s enormous consequences for international relations, human rights, and our understanding of state building. Stewart and Knaus parse carefully the philosophies that have informed interventionism―from neoconservative to liberal imperialist―and draw on their diverse experiences in the military, nongovernmental organizations, and the Iraqi provincial government to reveal what we can ultimately expect from large-scale interventions and how they might best realize positive change in the world. Author and columnist Fred Kaplan calls Can Intervention Work? ?the most thorough examination of the subject [of intervention] that I?ve read in a while.?
Includes bibliographical references
Keywords: Intervention (International law)